2018
DOI: 10.1136/gutjnl-2017-315062
|View full text |Cite
|
Sign up to set email alerts
|

IPMNs with co-occurring invasive cancers: neighbours but not always relatives

Abstract: This study demonstrates a higher prevalence of likely independent co-occurring IPMN and ductal adenocarcinoma than previously appreciated. These findings have important implications for molecular risk stratification of patients with IPMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 37 publications
9
88
0
1
Order By: Relevance
“…The main difference between the 2 molecular subtypes is whether the concurrent PDA arose from a common founder clone with a coexisting IPMN or from an entirely independent clone from the IPMN. The de novo subtype identified in this study may be consistent with the finding of Felsenstein et al 38 that indicated the independent development of PDA from concurrent IPMN. Moreover, the branch-off subtype could correspond to some cases in their study showing partially shared mutations between IPMNs and PDAs adjacent each other ( Figure 1A and B and Supplementary Figure 6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The main difference between the 2 molecular subtypes is whether the concurrent PDA arose from a common founder clone with a coexisting IPMN or from an entirely independent clone from the IPMN. The de novo subtype identified in this study may be consistent with the finding of Felsenstein et al 38 that indicated the independent development of PDA from concurrent IPMN. Moreover, the branch-off subtype could correspond to some cases in their study showing partially shared mutations between IPMNs and PDAs adjacent each other ( Figure 1A and B and Supplementary Figure 6).…”
Section: Discussionsupporting
confidence: 92%
“…Based on the histologic maps, 168 lesions (3-13 samples, with an average of 5.6 samples per patient) of invasive carcinomas, IPMNs, and MNLs were selected for molecular analysis. We evaluated 10 HG IPMN patients without invasive cancer who were sex-, age-, and epithelial type-matched with 30 patients with IPMN-related PDA to elucidate the heterogeneity of the IPMN progression (Supplementary Tables 1 and 2, cases [31][32][33][34][35][36][37][38][39][40].…”
Section: Histologic Evaluationmentioning
confidence: 99%
“…16 However, more recent data suggest that the rate could be as high as 18% (from molecular pathology series) and 28% (from surgical series). 18,19 Even in the current study by Oyama et al, 15 through the use of sophisticated molecular fingerprinting techniques, 30 of 68 (44%) of all pancreatic malignancies in the setting of BD-IPMN were concomitant PDACs, molecularly and often geographically distinct. 15 Whereas IPMN-derived carcinomas correlate with IPMN size and main pancreatic duct diameter, there are no radiologic IPMN cyst-related risk factors (eg, size, mural nodules, presence of cancer) for the development of these concomitant PDACs.…”
Section: Does Pancreatic Cyst Stability Justify Stopping Intraductal mentioning
confidence: 52%
“…Presence of KRAS mutation alone may not be sufficient to trace tumor cell clonality during PDA development and recurrence because hotspots are enriched in codons 12 and 13. When KRAS G12 D and G12V are found in multiple lesions, it is not easy to determine if they are clonally related or developed independently [7,8]. We therefore performed targeted sequencing to search for genes that are commonly mutated in human PDA [9], wherein we revealed a pathogenic mutation in SMAD4 across the specimens.…”
Section: Discussionmentioning
confidence: 99%